Directly from Galpha to protein kinase A: the kelch repeat protein bypass of adenylate cyclase - Peeters, Tom; Versele, Matthias; Thevelein, Johan M (Trends in biochemical sciences (Amsterdam. Regular ed.), 2007)
One major class of G proteins typically functions as heterotrimeric complexes consisting of Galpha, Gbeta and Ggamma subunits. However, recent work in yeast has identified an atypical Galpha protein, Gpa2p, which functions without cognate Gbetagamma subunits. Two novel kelch repeat protein binding partners of Gpa2p, Krh1p and Krh2p, do not function as alternative Gbeta subunits, as initially thought, but rather as Gpa2p effectors. They directly link Gpa2p to protein kinase A, thus forming an adenylate cyclase bypass pathway that enables inputs other than cellular cAMP concentration to affect protein kinase A activity. Because mammalian protein kinase A expressed in yeast is also subject to control by the same bypass pathway, it is exciting to postulate that a functionally similar mechanism might exist in mammalian cells, and that other Galpha proteins could exhibit similar characteristics to Gpa2p.